ON THE ISSUE OF THE MEANING AND CONCEPT OF SCIENTIFIC AND EXPERT SUPPORT FOR PARLIAMENTARY ACTIVITIES - Dmitry Rakhmanov (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
The article is devoted to the issues of the meaning and concept of scientific and expert support of parliamentary activities. In it, these issues are revealed from the point of view of the development of parliamentary and more active involvement of representatives of the expert community in various areas of parliamentary activity. Scientific and expert support of parliamentary activities is important in terms of strengthening the scientific validity of the issues considered by the parliament, especially, in the activity on the adoption of laws, other important strategic documents that determine the priority areas of domestic and foreign policy. It is noted that in recent years, such involvement of scientists, experts, specialists from various fields of knowledge, representatives of civil society has become a vital necessity. This ensures constant communication between the parliament and various sectors of society, timely identification of problems that concern citizens and, most importantly, the search for the most optimal and scientifically verified ways to solve them. The issues of the significance and concept of scientific and expert support of parliamentary activities are considered by the author through the prism of national experience, in particular, the activities of the Parliament of Uzbekistan - the Oliy Majlis, as well as with a wide retrospective of the opinions of Uzbek and Russian scientists on this issue